UPAYA KADER SURABAYA HEBAT DALAM MENCIPTAKAN LINGKUNGAN SEHAT DI KELURAHAN GUNUNG ANYAR TAMBAK KOTA SURABAYA - Yunita Ayu Wulandari; Chabib Musthofa (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Great Surabaya Cadres (KSH) play an important role in maintaining and creating a healthy environment in the village through various programs directed by the government. These programs include: PSN activities (eradication of mosquito nests), 5 pillar STBM, TOGA survey, waste sorting and posyandu. Apart from that, ongoing education is needed and the cadres have succeeded in increasing public awareness regarding the importance of maintaining a clean and healthy environment. The aim of this research is that KSH helps empower communities to actively participate in managing their own environment. The method used is qualitative with a descriptive approach, namely collecting data or information based on facts in the field. The location of the research carried out was at RT 08 RW 03, Gunung Anyar Tambak Village, Gunung Anyar District, Surabaya City. The research subject focuses on the women of the Great Surabaya Cadre (KSH) using data collection techniques, namely interviews, observation and documentation. The results of this research are that KSH's efforts in creating a healthy environment have been successful and made the environment beautiful and radiant.